Constructing Ambient Intelligence AmI 2011 Workshops, Amsterdam, The Netherlands, November 16-18, 2011. Revised Selected Papers - Wichert, Reiner; Laerhoven, Kristof Van.; Gelissen, Jean.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the refereed proceedings of the AmI 2011 Workshops, held in Amsterdam, The Netherlands, in November 2011. The 55 revised full papers presented were carefully reviewed and selected from numerous submissions. The papers are organized in topical sections on aesthetic intelligence: designing smart and beautiful architectural spaces; ambient intelligence in future lighting systems; interactive human behavior analysis in open or public spaces; user interaction methods for elderly, people with dementia; empowering and integrating senior citizens with virtual coaching; integration of AMI and AAL platforms in the future internet (FI) platform initiative; ambient gaming; human behavior understanding: inducing behavioral change; privacy, trust and interaction in the internet of things; doctoral colloquium.
Keywords: Computer science; Computer communication systems; Information storage and retrieval; User interfaces (Computer systems).; Artificial intelligence; Computers and civilization; Computer Science; Information Systems Applications (incl. Internet).; Computer Communication Networks; User Interfaces and Human Computer Interaction; Artificial Intelligence (incl. Robotics).; Information Storage and Retrieval; Computers and Society; Electronic books